Visualizing landmark-based face morphing traces on digital images - Batskos, Ilias; Spreeuwers, Luuk; Veldhuis, Raymond (Frontiers in Computer Science, 2023)
As This paper focuses on an identity sharing scheme known as face image morphing or simply morphing. Morphing is the process of creating a composite face image, a morph, by digitally manipulating face images of different individuals, usually two. Under certain circumstances, the composite image looks like both contributors and can be used by one of them (accomplice) to issue an ID document. The other contributor (criminal) can then use the ID document for illegal activities, which is a serious security vulnerability. Therefore, the investigation of morphing is both important and urgent. The ability to visualize image manipulation traces related to morphing is a field that has not received much attention. Here we evaluate the effectiveness and the limitations of two image forensics methods in visualizing morphing related traces in digital images under certain realistic conditions. Our ability to visualize is not only important as forensic evidence but also for analyzing the characteristics of different morphing algorithms that are widely available online, which could lead to the development of algorithm specific feature extraction strategies for automated detection.